Edukasi Akupresur dan Air Jahe Atasi Dismenore di Posyandu Remaja Kelurahan Danau Sipin Kota Jambi - Julaecha, Julaecha; Wuryandari, Ajeng Galuh (Jurnal Abdimas Kesehatan (JAK), 2026)
Dysmenorrhea is lower abdominal pain that sometimes radiates to the waist, lower back, and thighs. Dysmenorrhea is often experienced by some women of productive age, which can affect daily activities and quality of life, so treatment is needed to relieve the symptoms that arise. It can be done pharmacologically and non-pharmacologically to help overcome pain, including with a number of spices, acupressure, warm compresses, aromatherapy. One of the non-pharmacological therapies is acupressure or pressure on certain points can stimulate blood circulation and the release of endorphins as a natural analgesic, while ginger therapy has a fairly high essential oil content and gingerol content can block prostaglandins so it can reduce pain during menstruation. This community service aims to provide education on how to overcome menstrual pain with acupressure and giving ginger water to teenagers. The method used is educational approach through counseling about dysmenorrhea and how to overcome it as well as demonstrations about acupuncture points to overcome menstrual pain and how to do acupressure and how to make ginger water to be consumed during dysmenorrhea. The results of community service about acupressure education and ginger water to overcome dysmenorrhea after counseling on adolescents have been proven to be educationally able to increase the knowledge and skills of adolescent girls in overcoming pain during dysmenorrhea as well as a preventive effort for adolescent girls to overcome dysmenorrhea with non-pharmacological therapy that is easy to do and can be done independently so that they can feel the benefits optimally with natural methods